Gender and engagement in automated online test feedback in first year human biology - Sanders, K.; Hill, J.; Meyer, J.; Fyfe, Georgina; Fyfe, Susan; Ziman, M.; Koehler, N. (Ascilite, 2007)
This study reports on the differential use and benefits for males and females of the provision of automated feedback for online MCQ tests in first year Human Biology. The study was conducted across three Western Australian universities offering first year Human Biology units to approximately 2000 students per year. We found that immediate feedback benefits the learning of both sexes, but greater male engagement is obtained through shorter feedback tasks.